2008
DOI: 10.1016/s1726-4901(08)70004-2
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Aerodigestive Tract Flexible Endoscopy as an Outpatient Procedure in Young Children

Abstract: From this study, we conclude that FE is a safe, effective and tolerable outpatient procedure in the majority of young children, and serious complications were uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Three decades after the pioneering work of Wood,8, 9 FB has been well recognized as a low‐risk and high‐yield clinical tool for evaluating various airway problems in pediatrics and neonates in a number of studies 6, 7, 10, 15, 23–25. Recently, we also reported that FB can be safely applied to both inpatients and outpatients 4, 10, 19, 22, 23. In the description of Nussbaum,26 no related mortality was found in 2,836 FB procedures performed on both pediatric ICU and ambulatory patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three decades after the pioneering work of Wood,8, 9 FB has been well recognized as a low‐risk and high‐yield clinical tool for evaluating various airway problems in pediatrics and neonates in a number of studies 6, 7, 10, 15, 23–25. Recently, we also reported that FB can be safely applied to both inpatients and outpatients 4, 10, 19, 22, 23. In the description of Nussbaum,26 no related mortality was found in 2,836 FB procedures performed on both pediatric ICU and ambulatory patients.…”
Section: Discussionmentioning
confidence: 99%
“…During the past 18 years, we have developed and used a novel technique17 which, in our experience, is helpful to provide oxygenation and assist ventilation in patients when performing the FB procedure. This allows for a wider and more invasive application of FB,18–23 especially for ICU patients who already show signs of cardiopulmonary compromise. The aim of this study is to retrospectively review our experience with FB in pediatric ICU patients of the last 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…The Traditionally, being widely available and easy to use, flexible endoscopy is considered the first and essential visual inspection instrument of AET. [26][27][28] Hypoxia and hypoventilation are frequent adverse effects during pediatric flexible endoscopy; therefore, supplemental oxygen and PPV are highly recommended. [23][24][25] Without pneumatic stenting effect of SPI, the PLS remains collapsed and flexible endoscopy cannot evaluate the posterior commissure of the larynx, 29 as seen in the case of the seven infants referred whose laryngeal cleft failed to be detected.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, being widely available and easily handled, FE plays an essential role in exploring lesions that cause airway and respiratory problems in pediatric patients. [24][25][26] However, FE has not been considered a commendable tool to evaluate the posterior commissure of the larynx where lesion as LC may fail to recognize. 27 RE is more capable and remains the gold standard for confirmation of LC.…”
Section: Discussionmentioning
confidence: 99%